2014
DOI: 10.1063/1.4870319
|View full text |Cite
|
Sign up to set email alerts
|

Electroplated Fe films prepared from a deep eutectic solvent

Abstract: Electroplating of Fe films was carried out from choline chloride-ethylene glycol types of DES (Deep Eutectic Solvent). We investigated magnetic properties of the plated Fe films and evaluated the productivity for the electroplating process. Consequently, we found that surface morphology and current efficiency of the plated films were affected by the bath temperature. We obtained the Fe films with relatively smooth surface and high current efficiency in the bath temperature range from 70 to 110 C. The depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…37 As well, high temperature promotes the migration of ions leading to the significant increase of current density due to the anabatic thermal motion and the katabatic dynamic viscosity. 38,39 The conductivities of the Co-Sn-Ethaline electrolyte at 25, 50 and 75 • C are measured to be 8.32, 11.30 and 14.25 μS cm −1 , respectively. As shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…37 As well, high temperature promotes the migration of ions leading to the significant increase of current density due to the anabatic thermal motion and the katabatic dynamic viscosity. 38,39 The conductivities of the Co-Sn-Ethaline electrolyte at 25, 50 and 75 • C are measured to be 8.32, 11.30 and 14.25 μS cm −1 , respectively. As shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] We have reported Fe, Fe-Ni and Fe-Co films prepared in DES-based plating baths, and confirmed high current efficiency of the plating process. [9][10][11] As some Fe-Ni-Co films with high saturation magnetization and low coercivity have been reported using aqueous plating baths 12 and sputtering method, 13,14 we also focused on Fe-Ni-Co ternary alloy. In this study, we investigated the structural and the magnetic properties of the Fe-Ni-Co films plated in the DES-based plating bath.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there have been some reports on magnetic films such as Ni, Co, Ni-Co, Ni-Co-Sn, Sm-Co, and Co-Pt prepared from DESbased baths, [3][4][5][6][7][8][9][10] and we have also reported Fe and Fe-Ni films prepared in DES-based plating baths. 11,12 In our previous studies, we confirmed that the plating processes from the DES-based baths for the Fe and the Fe-Ni films have high current efficiency (>90%). As high current efficiency of the plating processes for Ni films were also reported by Motoyama et al, 13 the DES is one of hopeful solvents for the magnetic films.…”
Section: Introductionmentioning
confidence: 51%